Arteritic Orbital Ischemia Producing Afferent and Efferent Pupillary Defects. Issue 4 (December 2020) - Hussain, Mariam; Kini, Ashwini; Al Othman, Bayan; Ponce, Claudia Prospero; Li, Helen; Lee, Andrew G.
Abstract : Abstract: A 67-year-old woman presented with acute loss of vision to no light perception (NLP), a right afferent pupillary defect, and anisocoria with a nonreactive and dilated pupil in the right eye. Fundus examination showed pallid optic disc edema and a central retinal artery occlusion (CRAO) in the right eye. A temporal artery biopsy showed giant cell arteritis (GCA). Orbital involvement in GCA has been reported previously. However the combination of an afferent and efferent pupillary defect, NLP vision, pallid disc edema, and a CRAO in an elderly patient is likely a unique clinical combination that should strongly suggest GCA. Clinicians should be aware of the myriad presentations of GCA, including orbital ischemia.